KAJIAN SEMIOTIK PADA SYAIR GULUNG KETAPANG KARYA MAHMUD MURSALIN - Rusadi, Luthfiah; Priyadi, A Totok; Wartiningsih, Agus (Universitas Tanjungpura, 2023)
This was aimed to describe, analyze, and interpret the analysis results of the icons, indexes, and symbols in Mahmud Mursalin's Syair Gulung Ketapang and is implementation into a learning material. The method applied in this study was descriptive in the form of qualitative research with a semiotic approach. Source of data in this study was Syair Gulung Ketapang by Mahmud Mursalin. Data gathered was icons, indexes, and symbols in the form of words, phrases, or sentences contained in Syair Gulung. Data was collected using documentary study technique with the researcher herself as a data collection tool. According to data analysis results, there were found 352 data from the three analyses. The research results can be implementes into Bahasa Indonesia instructions in schools about concluding the content of poetry at junior high school level or its equivalent in class VII, even semester, especially on Basic Competence (KD) 3.13 and 4.13 in curriculum 2013.